Gas phase temperature measurements in the liquid and particle regime of a flame spray pyrolysis process using O2-based pure rotational coherent anti-Stokes Raman scattering - Peukert, Wolfgang; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Seeger, Thomas; Leipertz, Alfred (Applied Optics, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used where mostly oxygen is fed to the flame if high combustion temperatures and thus small primary particle sizes are desired. To improve the understanding of these complex processes in situ, noninvasive optical measurement techniques were applied to characterize the extremely turbulent and unsteady combustion field at those positions where the particles are formed from precursor containing organic solvent droplets. This particle-forming regime was identified by laser-induced breakdown detection. The gas phase temperatures in the surrounding of droplets and particles were measured with O2 -based pure rotational coherent anti-Stokes Raman scattering (CARS). Pure rotational CARS measurements benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. Due to different signal disturbing processes only the minority of the collected signals could be used for temperature evaluation. The selection of these suitable signals is one of the major problems to be solved for a reliable evaluation process. Applying these filtering and signal selection steps temperature measurements have successfully been conducted. Time-resolved, single-pulse measurements exhibit temperatures between near-room and combustion temperatures due to the strongly fluctuating and flickering behavior of the particle-generating flame. The mean flame temperatures determined from the single-pulse data are decreasing with increasing particle concentrations. They indicate the dissipation of large amounts of energy from the surrounding gas phase in the presence of particles.
Keywords: oxyide; nanoparticle; optical; noninvasive; droplet; combustion; raman; scattering